ANÁLISE DE ENVOLTÓRIA EM HABITAÇÃO DE INTERESSE SOCIAL PELO MÉTODO SIMPLIFICADO DA INI-R. - Willian Zimi Ortega Padilha (2023)
After a period marked by a significant lack of investment in public housing, Brazil witnessed a revitalization of the sector, gaining momentum through the Programa de Aceleração do Desenvolvimento (PAC) and subsequently, the Programa Minha Casa Minha Vida (PMCMV). Although the launch of PMCMV coincided with a global financial crisis, its ability to sustain investments in the construction industry is noteworthy. However, it is crucial to assess its effectiveness in addressing ever-evolving housing needs. In this context, this work focuses on envelope analysis using the simplified INIR method in a specific block of a Social Housing (HIS) development. The initial phase of the work involved the use of BIM software to assess solar radiation on the envelopes of Autonomous Housing Units (UHs) in a residential complex located in Campo Grande, Mato Grosso do Sul. The result of this analysis directed the selection of a particular block, based on the highest solar radiation recorded on its façade surfaces. Subsequently, the selected block underwent a comprehensive evaluation of thermal envelope performance using the simplified INI-R method from PBE Edifica. The technical results obtained led to substantial discussions that indicated unsatisfactory performance of the analyzed Autonomous Housing Units (UHs). This study addresses issues related to the thermal performance of buildings, as well as the significance of bioclimatic architecture as a critical tool for devising strategies to enhance thermal comfort in built environments. Furthermore, it underscores the ongoing need for adaptation and improvement of social interest housing programs in Brazil to meet constantly evolving housing demands and provide efficient housing solutions that promote the well-being and quality of life of the population.